Cytotoxicity and apoptotic effects of the ethyl acetate fraction of Zanthoxylum acanthopodium DC fruit on B16F10 melanoma cell culture - Megawati, Eka; Bangun, Hakim; Putra, Imam; Rusda, Muhammad (Contemporary Oncology/Współczesna Onkologia, 2025)
This study aimed to investigate the cytotoxicity and apoptotic effects of the ethyl acetate fraction of Zanthoxylum acanthopodium DC (ZA) fruit on B16F10 melanoma cell cultures. Material and methods: The ethyl acetate fraction was obtained through maceration followed by fractionation with n-hexane and ethyl acetate. Cytotoxicity was assessed using the MTT assay to determine the IC50 value. B16F10 melanoma cells were then grouped into control, IC50, ¾ IC50, ½ IC50, and doxorubicin groups. Apoptosis induction was analysed using Annexin V and caspase-3 expression assays. Results: The ethyl acetate fraction of ZA fruit exhibited cytotoxic activity on B16F10 melanoma cells, with an IC50 value of 249.3 µg/ml. Apoptosis induction was confirmed by a significant increase in caspase-3 expression compared to the control group (p < 0.05). Conclusions: The ethyl acetate fraction of ZA fruit demonstrated cytotoxic effects and induced apoptosis in B16F10 melanoma cells, potentially through caspase-3 activation.